2004
DOI: 10.1161/01.str.0000120726.69501.74
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Enhancement and Contrast Extravasation on Computed Tomography After Intra-Arterial Thrombolysis in Patients With Acute Ischemic Stroke

Abstract: Background and Purpose-The goal of this study was to determine the CT findings and clinical consequences of contrast enhancement and contrast extravasation on CT scans obtained after intra-arterial thrombolytic therapy for treatment of acute ischemic stroke. Methods-Sixty-two patients were treated with intra-arterial thrombolysis. All patients underwent nonenhanced CT scans immediately and 24 hours after thrombolytic therapy. Contrast enhancement was defined as a hyperdense lesion that disappeared on a 24-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
167
6
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(193 citation statements)
references
References 24 publications
15
167
6
5
Order By: Relevance
“…Occlusion site and perfusion defect size are important considerations in determining the outcome of revascularization procedures and defining a target population for treatment (47)(48)(49). Surrogate radiologic markers of BBB breakdown, including intraprocedural early venous filling (50) and postprocedural contrast enhancement and extravasation, have been described previously (51). These markers usually are associated with larger volumes of contrast material injected over a prolonged period.…”
Section: Discussionmentioning
confidence: 95%
“…Occlusion site and perfusion defect size are important considerations in determining the outcome of revascularization procedures and defining a target population for treatment (47)(48)(49). Surrogate radiologic markers of BBB breakdown, including intraprocedural early venous filling (50) and postprocedural contrast enhancement and extravasation, have been described previously (51). These markers usually are associated with larger volumes of contrast material injected over a prolonged period.…”
Section: Discussionmentioning
confidence: 95%
“…Repeated microcatheter contrast injection may cause the extravasation of contrast to the surrounding tissue and thus result in toxic damage with resultant hemorrhage. 15 As a result, operators repeating microcatheter injections should take care to reduce injection pressure and volume. Microwire maceration of the clot also carries the risk of penetration into perforator branches with resultant hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast extravasation has been described as a hyperdense area that disappears on a follow-up CT scan (14). Mericle et al (15) have suggested that extravasation of contrast medium could be defined as a hyperdense area with a maximal HU measurement over 90 and/or disappearance of the hyperdensity on a repeated CT obtained within 24 hours.…”
Section: Discussionmentioning
confidence: 99%